First detection of Russian wheat aphid Diuraphis noxia Kurdjumov (Hemiptera: Aphididae) in Australia: a major threat to cereal production. Issue 4 (17th August 2017) - Yazdani, Maryam; Baker, Greg; DeGraaf, Helen; Henry, Ken; Hill, Kelly; Kimber, Bill; Malipatil, Mallik; Perry, Kym; Valenzuela, Isabel; Nash, Michael A
Abstract: Invasive pest species pose a major threat to agricultural production around the world. Until recently, the Russian wheat aphid, Diuraphis noxia Kurdjumov, a major pest of wheat and barley crops worldwide, was considered a high‐priority exotic pest threat to the Australian grains industry. Here, we document the initial detection and establishment of D. noxia in Australia in 2016. These are the first records for this genus from South Australia, Victoria and New South Wales. Morphological and molecular information is presented for confirmed diagnosis of the species based on voucher specimens. Known distribution data are provided, along with a list of Poaceae hosts on which D. noxia has been recorded, and a brief description of the typical damage symptoms caused by these aphids. The potential impact of this aphid on Australian cereal production is discussed, and we identify research areas required to underpin future management of this new threat to the Australian cereal industry.